Primary Design and Optimization of Dehydroascorbate reductase (DHAR) Gene Amplification in Oryza sativa L. - Putri, Isna Aryunita Putri; Achyar, Afifatul; Zulzusri, Zulzusri; Atifah, Yusni; Putri, Dwi Hilda; Violita, Violita (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2023)
Dehydroascorbate reductase (DHAR) is one of the antioxidant enzymes involved in ascorbate recycling which catalyzes the reduction of oxidized ascorbate. DHAR is responsible for regenerating AsA from its oxidized state and regulating the redox state of cellular AsA which ultimately influences cell response and tolerance to ROS. DHAR is important for plant growth because it plays a role in the recycling of AsA. Rice is a plant that is sensitive to drought stress, one of the defense mechanisms of plants in dealing with drought stress is to activate the DHAR gene. The method that can be used to amplify the Dehydroascorbate reductase (DHAR) gene is by qRT-PCR. This method requires specific primers for the target gene. However, for now, the primary design of the DHAR gene is unknown. This study aims to design suitable primers for the amplification of DHAR target genes using the qRT-PCR technique, and to determine the optimal annealing temperature. Primer design was carried out using the PrimerQuest program, then viewed and then analyzed using GeneiousPrime, after which it was checked for specificity with primerBLAST. The primary design results with the best criteria were Forward DHAR 5'-GTACCCAACCCCGTCTCTTG -3' and Reverse DHAR 5'- TGGTAGAGCTTTGGTGCCAG -3' primers with a product size of 228 bp with an optimal temperature for PCR of 60ºC.